In Favour of a Fund to Stabilise Commodity Exporters' Income - Cohen, Daniel (OECD Development Centre Policy Insights, 2007)
Poor countries will remain vulnerable to external shocks from export prices or from natural disasters for some time. Indeed, the lowest income countries have an even higher incidence of such adverse events than other developing countries and tend to suffer larger damages when they occur